2003
DOI: 10.1016/s0925-4439(03)00095-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences between the susceptibility Z−2/C−106 and protective Z+2/T−106 promoter region polymorphisms of the aldose reductase gene may account for the association with diabetic microvascular complications

Abstract: Studies have shown that polymorphisms located at positions -106 and approximately -2100 base pairs (5'ALR2) in the regulatory region of the aldose reductase gene are associated with susceptibility to microvascular complications in patients with diabetes. The aim was to investigate the functional roles of these susceptibility alleles using an in vitro gene reporter assay. Susceptibility, neutral and protective 5'ALR2/-106 alleles were transfected into HepG2 cells and exposed to excess D-glucose (D-glucose at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…Our previous study (24) found a highly significant difference in the luciferase activities between the recombinants that contain different AKR1B1 gene haplotypes that had been transfected into Hep G 2 cells exposed to high glucose. The present study confirmed that the Z-2/C-106 and Z/C-106 haplotypes have the highest transcription activities, and silencing of NFAT5 expression reduced the transcription activity of AKR1B1 even under high-glucose conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous study (24) found a highly significant difference in the luciferase activities between the recombinants that contain different AKR1B1 gene haplotypes that had been transfected into Hep G 2 cells exposed to high glucose. The present study confirmed that the Z-2/C-106 and Z/C-106 haplotypes have the highest transcription activities, and silencing of NFAT5 expression reduced the transcription activity of AKR1B1 even under high-glucose conditions.…”
Section: Discussionmentioning
confidence: 97%
“…SiRNA-569R or inv569R at 400 nmol/l or No-siRNA as controls was transfected into the HEK 293 cells. For analysis of AKR1B1 transcription, pGL3 reporter plasmids at 98 ng, which contain the promoter region with three OREs and different haplotypes of the AKR1B1 gene (24) and firefly luciferase gene downstream, were cotransfected with pRL-TK control plasmids at 2 ng, which contain the Renilla luciferase gene into the cells at 24 h after siRNA transfection. The next day, cells were divided into two groups: 1) cells maintained in original media and 2) cells switched to high-glucose conditions (31 mmol/l of D-glucose) for another 48 h or hypertonic conditions (extra 50 mmol/l NaCl) for another 20 h as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…Polymorphism in the retinoid-X receptor (RXR) gamma gene has also been associated with DR (OR = 2.388; 95% confidence interval = 1.17-4.875) in Asians with T2D [126]. Polymorphisms in the regulatory region of the aldose reductase (ALR2) gene (encoding the rate-limiting enzyme of the polyol pathway) were associated with susceptibility to DN and DR [114,127]. However, the impacts of these genetic risk factors were modest, and some studies yielded inconsistent findings [128,129].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Animal species that are deficient in ALR2 gene expression in lens, such as the mouse, are relatively resistant to the onset of diabetic cataracts [25]. In contrast, genetic polymorphisms linked to the human AKR1B1 gene have been associated with higher tissue levels of ALR2 and development of more advanced diabetic retinopathy [20, 31]. …”
Section: Introductionmentioning
confidence: 99%